THE INFLUENCE OF TIKTOK SHOP VIDEO ADS ON CONSUMER PURCHASE INTENTION USING THE TAM2 APPROACH IN UNIVERSITY STUDENTS - Fadhia Hayya, Aqiella; Wibowo, Kunto Adi; Fuady, Ikhsan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This research aims to examine the influence of perceived playfulness, perceived usefulness, and personalized product recommendations on purchase intention in TikTok Shop among university students. The study involved 217 respondents who completed questionnaires related to demographic characteristics, frequency of TikTok usage, and their purchasing behavior. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships between the variables. The findings indicate that all proposed hypotheses were supported. Perceived playfulness and perceived usefulness significantly influence purchase intention, with personalized product recommendations affecting both perceived playfulness and perceived usefulness. The model also demonstrated that personalized recommendations directly influence purchase intention. These results suggest that TikTok Shop's effectiveness in enhancing user experience and increasing purchase intention is significantly driven by the perceived enjoyment and usefulness of the platform, as well as the role of personalized product recommendations. The study contributes to understanding the factors that drive purchase intention in the context of social media-based e-commerce.